Written representation of spoken interaction in the official parliamentary transcripts of the Finnish Parliament - Voutilainen, Eero (Frontiers in Communication, 2023)
In this article, I will analyze the written representation of spoken interaction in the official plenary session transcripts of the Finnish Parliament. The official parliamentary transcripts are not—and cannot be—identical copies of the original speech event. Instead, they are linguistically and textually edited in many ways. I will examine the different types of editorial changes that are made in the official Finnish parliamentary transcripts. These include phonological, morphological, and syntactic alterations, editing out of self-repairs, planning expressions, stuttering and slips-of-tongue, and finding written ways of expression for phenomena such as pauses, prosody, gestures, and non-verbal events. I will also discuss how the editorial changes affect the written representation of plenary session interaction.